Case report: Major pathologic response induced by neoadjuvant treatment using BRAF and MEK inhibitors in a patient with stage IIIA lung adenocarcinoma harboring BRAF V600E-mutation - Liu, Chaoyuan; Lu, Min; Yang, Yang; Wang, Xiang; Ma, Fang; Liu, Xianling (Frontiers in Oncology, 2022)
Targeted therapy has achieved great success in advanced non-small lung cancer (NSCLC) with driver gene and neoadjuvant targeted therapy is increasingly being investigated. Though neoadjuvant targeted therapy with EGFR-TKI and ALK-TKI showed good efficacy, there is no report of neoadjuvant targeted therapy to BRAF V600E mutation on NSCLC so far. Here, we report the first case of successful neoadjuvant targeted therapy with BRAF and MEK inhibitors followed by radical surgical excision with major pathologic response(MPR) in a patient with stage ⅢA lung adenocarcinoma (LUAD) harboring BRAF V600E mutation. The case informs us that targeted therapy with BRAF and MEK inhibitors could be administrated as a neoadjuvant strategy for selected cases of NSCLC harboring BRAF V600E mutation.